A Qualitative Study to Explore the Determinants of Risky Sexual Behaviors and Pregnancy among Female Adolescents in Sabah, Malaysia. (28th November 2022) - Idris, Idayu Badilla; Bin Sulaiman, Shameer Khan; Hod, Rozita; Khazaei, Hamed; Abdullah, Nik Nairan
Abstract : This investigation was performed in Kota Kinabalu, Sabah state, where the highest number of pregnancies is recorded. The purpose of this study was to determine variables associated with hazardous sexual activity and adolescent pregnancy in Sabah, Malaysia. The findings indicate that familial variables, peer interactions, self-esteem, psychiatric concerns, economic considerations, and sex knowledge all play a significant role in hazardous sexual conduct and adolescent pregnancy in Sabah, Malaysia. Information obtained from this study will help the Malaysian government and other officials to design and establish proper interventions that will help alleviate the challenge of high prevalence of teenage pregnancy. It is suggested that sex education be included in the high school curriculum, along with physical and health education in Sabah, Malaysia.